2021
DOI: 10.20527/iis.v2i2.3076
|View full text |Cite
|
Sign up to set email alerts
|

The Urgency of Local Wisdom Content in Social Studies Learning: Literature Review

Abstract: Kearifan lokal merupakan karaterisitk masyarakat di suatu daerah yang harus dijaga sebagai identitas konstruktif sekaligus sebagai filter bagi berbagai aspek kebudayaan luar yang destruktif. Dalam konteks demikian, kearifan lokal dipahami sebagai warisan dari generasi ke generasi agar tidak tergerus beragam unsur-unsur kebuduyaan luar. Karena itu pembelajaran kearifan lokal merupakan kebutuhan yang tidak terelakkan, satu diantaranya melalui pembelajaran Ilmu Pengetahun Sosial (IPS). Pembelajaran IPS merupakan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 9 publications
0
19
0
4
Order By: Relevance
“…From the description above, it can be concluded that the Soto Bang Amat restaurant also needs panting music workers to attract tourists. Both local and foreign tourists (Jumriani, 2021). In the era of development, it is increasingly rare for restaurants to provide space for essential music artists to perform.…”
Section: Resultsmentioning
confidence: 99%
“…From the description above, it can be concluded that the Soto Bang Amat restaurant also needs panting music workers to attract tourists. Both local and foreign tourists (Jumriani, 2021). In the era of development, it is increasingly rare for restaurants to provide space for essential music artists to perform.…”
Section: Resultsmentioning
confidence: 99%
“…Pendidikan IPS penting diberikan kepada peserta didik di tingkat sekolah dasar agar mereka mampu mengenal kehidupan masyarakat dan lingkungan dengan didukung media pembelajaran seperti media cetak, media elektronik, media sosial bahkan secara langsung melalui pengalaman hidup sehari-hari di tengah masyarakat. Sebagaimana pembelajaran pendidikan IPS lebih mengedepankan aspek "Pendidikan" dari pada "Transfer Konsep" (Jumriani et al, 2021;Mariati et al, 2021), karena dengan belajar pendidikan IPS peserta didik diharapkan mendapatkan sejumlah pemahaman beberapa konsep tentang sikap, nilai, moral, dan keterampilan untuk menjalani kehidupan sehari-hari. Pendidikan IPS memiliki ciri khas kajian yang terintegrasi (terpadu), interdisipliner, multidisipliner, bahkan krosdisipliner.…”
Section: Pendahuluanunclassified
“…This is because local wisdom is a characteristic of a community group in a certain area. Local wisdom can be in the form of rules, activities, or ideas as a guide for community behavior (Jumriani et al, 2021). Character education through education that is based on local wisdom presented in learning is one of the paths that must be taken by teachers (Relin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%